Participatory forest Management Objectives in India - Jattan, S. S.; , Pratima (Indian Forester, 2001)
The forests in India are required to meet diverse demands and setting of management objectives, consequently, presents problems. The management objectives were adjusted to meet the national requirements and were accordingly reflected in the National Forest Policies of 1894,1952 and 1988. Management objectives are still not clear in respect of protection, production and social functions of the forests. Forest management objectives need clarity to ensure sustainability of forest management practices. Forestry cannot be viewed in isolation from other land based husbandry systems. Holistic approach for land resource management is necessary.